Kajian Bioekologi Ikan Dominan Sebagai Bioindikator Kesehatan Lingkungan Di Muara Sungai Kumbe Kabupaten Merauke - elviana, sisca; sunarni, Sunarni (Universitas Islam Lamongan, 2023)
River estuaries are a habitat for various aquatic-associated organisms both in the water, on the soil surface and that immerse themselves in the soil. The purpose of this study was to study the bioecology of fish as a bioindicator of environmental health in the Kumbe River Muara, Merauke Regency. This research took place from September to November 2022, carried out along the Kumbe River estuary, Merauke Regency. The data collection method was carried out by purposive sampling and interviews. The results showed that the most abundant species found was snapper (Lates Calcarifer) while the least found was parang fish (Chirocentrus dorab). The diversity index shows the medium category, the uniformity value shows the community is stable and the dominance index shows the dominance value in the area is high. The environmental parameters measured were pH, temperature and salinity. The results showed that it was still in accordance with the quality standards for aquatic biota. The long-weight relationship based on representative fish was found to be dominant, namely snapper (Lates Calcarifer), tilapia (Oreochromis niloticus) and spiny fish (Arius sp.) showing a negative allometric growth pattern. Allometric growth shows that the length growth is not balanced with the weight growthKeywords : Bioecology, Fish, Kumbe River